Implementation of Hypnotherapy in Burn Pain Patients with Pain: A Case Report - Pramadita, Pegi Karinda; Azimatul Karimah (Faculty of Medicine, Universitas Airlangga, 2025)
Introduction: Burn-related pain significantly impacts patients both physiologically and psychologically. Pain and associated psychosocial issues, such as anxiety and fear, can intensify the patient’s suffering. Effective pain management for burn patients includes both pharmacological and non-pharmacological interventions. Methods: A patient diagnosed with severe burns (24% total body surface area, deep dermal/full-thickness) was treated in the intensive care unit of Dr. Soetomo Hospital, undergoing debridement on the chest and left arm. The patient reported severe pain (VAS 7) and anxiety (HAM-A 26). Anxiety, particularly related to anticipation of treatment, appeared to exacerbate pain perception. The therapist assessed the patient’s understanding, beliefs, and expectations about their condition. Hypnotherapy was administered over five days, including pre-induction (assessing expectations), induction, relaxation, deepening, analgesic suggestion, and termination phases. Results: Following five sessions of hypnotherapy, the patient’s pain score decreased from VAS 7 to 2, and anxiety level reduced from HAM-A 26 (severe) to 16 (mild). The patient also received intravenous metamizole (3×150 mg), ceftazidime (2×300 mg), oral fluoxetine (1×20 mg), and clobazam (1×5 mg) during hospitalization. Conclusion: Hypnotherapy proved to be an effective non-pharmacological intervention in reducing pain and anxiety in a burn patient. It can be integrated alongside conventional treatment in various clinical settings, offering a complementary approach for managing anxiety-related burn pain.